Estimated employment and gross national product impacts of 1989 tourism in Ireland - Henry, E. W. (Statistical and Social Inquiry Society of Ireland, 1991)
The employment and Gross National Product (GNP) impacts of 1989 Tourism in Ireland are estimated by Input-Output methodology. Outof- state Revenue plus Carrier Receipts during 1989 imply some 51,000 manyears of employment and #971m of GNP throughout the Irish economy, by way of direct, indirect and induced impacts. The 1989 Domestic Tourist revenue has a further impact of about 13,000 manyears and #268m of GNP. These combined 1989 impacts of about 64,000 manyears and # l f239m of GNP may be regarded as lower limits, if one allows for some share of a further maximum 25,000 manyears and #36lm GNP due to implied Government income and respending, on a 'Balanced Budget' hypothesis. Irish GNP Normal multiplier results are found to be compatible with similar multipliers from other parts of the world.
Read before the Society, 9 May 1991
Keywords: Tourist industry; Tourism sector; 314.15